Vegetative compatibility groups among isolates of Aspergillus flavus from sesame seed in Iran and mycotoxin production - HABIBI, AZADEH; BANIHASHEMI, ZIA (Phytopathologia Mediterranea, 2008)
The genetic diversity of a population of Aspergillus fl avus isolated from sesame seeds collected in 2004 and 2005 from various parts of Iran was studied through vegetative compatibility, and their mycotoxin production was determined. Sixteen vegetative compatibility groups (VCGs) were identified among the nit mutants. VCGs were not evenly distributed through Iran. With few exceptions, there was a relationship between a VCG and the amount of mycotoxins produced by its isolates.